Highlights in the knowledge of brown spider toxins. Issue 1 (December 2017) - Chaves-Moreira, Daniele; Senff-Ribeiro, Andrea; Wille, Ana; Gremski, Luiza; Chaim, Olga; Veiga, Silvio
Abstract Brown spiders are venomous arthropods that use their venom for predation and defense. In humans, bites of these animals provoke injuries including dermonecrosis with gravitational spread of lesions, hematological abnormalities and impaired renal function. The signs and symptoms observed following a brown spider bite are called loxoscelism. Brown spider venom is a complex mixture of toxins enriched in low molecular mass proteins (4–40 kDa). Characterization of the venom confirmed the presence of three highly expressed protein classes: phospholipases D, metalloproteases (astacins) and insecticidal peptides (knottins). Recently, toxins with low levels of expression have also been found inLoxosceles venom, such as serine proteases, protease inhibitors (serpins), hyaluronidases, allergen-like toxins and histamine-releasing factors. The toxin belonging to the phospholipase-D family (also known as the dermonecrotic toxin) is the most studied class of brown spider toxins. This class of toxins single-handedly can induce inflammatory response, dermonecrosis, hemolysis, thrombocytopenia and renal failure. The functional role of the hyaluronidase toxin as a spreading factor in loxoscelism has also been demonstrated. However, the biological characterization of other toxins remains unclear and the mechanism by whichLoxosceles toxins exert their noxious effects is yet to be fully elucidated. The aim of this review is to provide an insight into brown spider venom toxins and toxicology, including a description of historical data already available in the literature. In this review article, the identification processes of novelLoxosceles toxins by molecular biology and proteomic approaches, their biological characterization and structural description based on x-ray crystallography and putative biotechnological uses are described along with the future perspectives in this field.